Spiritual Needs in Cancer Patients: A Narrative Review - Iyus Yosep; Rohman Hikmat; Ai Mardhiyah (Institute of Computer Science (IOCS), 2022)
Cancer is a life-threatening disease and causes physical, psychological, and spiritual problems for sufferers. The fulfillment of spiritual needs is one of the important things to improve the quality of life of cancer patients. However, health services still focus on fulfilling the physical aspect. So comprehensive data is needed regarding the spiritual needs of cancer patients. The purpose of this study was to comprehensively explore the fulfillment of spiritual needs in cancer patients. This study uses the Narrative Review method. Literature review through Ebsco, Pubmed, Science Direct, Sage Journals, and Google Scholar databases. The keywords used in English are